The accuracy of gypsum casts obtained from the disinfected extended-pour alginate impressions through prolonged storage times - Rania A. Sharif; Khalid M. Abdelaziz; Najla M. Alshahrani; Fatimah S. Almutairi; Mohrah A. Alaseri; Hoda L. Abouzeid; Mohamed F. A. Elagib (BMC, 2021)
Abstract Background Manufacturers of the extended-pour alginates claimed their dimensional stability through prolonged storage. No data confirmed the ability of these materials to maintain their dimensions and the reproduced oral details following their chemical disinfection. Therefore, this study evaluated the dimensional stability and surface detail reproduction of gypsum casts obtained from disinfected extended-pour alginate impressions through different storage time intervals. Methods Two hundred and forty three hydrocolloid impressions were made from one conventional (Tropicalgin) and two extended-pour (Hydrogum 5 and Chromaprint premium) alginates. These impressions were subjected to none, spray and immersion disinfection before their storage in 100% humidity for 0, 72 and 120 h. The dimensional stability and the surface detail reproduction were indirectly evaluated under low angle illumination on the resulted gypsum casts. At α = 0.05, the parametric dimensional stability data were analyzed using One-Way ANOVA and Tukey's comparisons, while the nonparametric detail reproduction data were analyzed using KrusKal Wallis and Mann-Whitney's tests. Results All gypsum casts exhibited a degree of expansion; however, the recorded expansion values did not differ between test categories (P > 0.05). Generally, casts obtained from spray-disinfected impressions showed lower detail accuracy (P < 0.05). Immersion-disinfected extended-pour alginates produced casts with better detail accuracy following 120 h of storage (P < 0.05). Conclusion All alginates materials offer comparable cast dimensions under different testing circumstances. Extended-pour alginates offer casts with superior surface details following their immersion disinfection and 120 h of storage. Spray-disinfection using 5.25% sodium hypochlorite affects the surface details of casts obtained from conventional and extended-pour alginates adversely.